2008
DOI: 10.1186/1471-2458-8-278
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of populations vaccinated in a public service and in a private hospital setting in the same area

Abstract: Background: Improving immunisation rates in risk groups is one of the main objectives in vaccination strategies. However, achieving high vaccination rates in children with chronic conditions is difficult. Different types of vaccine providers may differently attract high risk children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Considering the fact that Kumasi is an urban area with the majority clients being resident in Kumasi, this is consistent with the high proportion of deliveries in urban centres being supervised [ 7 ]. Hospital delivery has been associated with timely vaccine uptake [ 21 ] although in this study, children delivered in health facilities other than KATH received some vaccines later and is consistent with similar findings in Burkina Faso [ 19 ]. Further evidence in this study is the observed association between delivery in KATH and receipt of immunisation services in the same facility.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Considering the fact that Kumasi is an urban area with the majority clients being resident in Kumasi, this is consistent with the high proportion of deliveries in urban centres being supervised [ 7 ]. Hospital delivery has been associated with timely vaccine uptake [ 21 ] although in this study, children delivered in health facilities other than KATH received some vaccines later and is consistent with similar findings in Burkina Faso [ 19 ]. Further evidence in this study is the observed association between delivery in KATH and receipt of immunisation services in the same facility.…”
Section: Discussionsupporting
confidence: 88%
“…This study cannot determine the role of hospital birth in the timely administration of latter vaccines in the EPI schedule as these may be influenced by other factors. There may be the need to specifically examine the timeliness of vaccine uptake among children delivered outside hospitals to determine any relationship if it exists [ 19 ]. The fact that the majority of children in this study were delivered in a health facility is a marked deviation from national trends [ 7 ] and the results may therefore not be applicable to children delivered outside health facilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The calendar is regularly updated and published each year 5 . Although children with chronic diseases face greater risks, their vaccine coverage rates appear to be lower than in the general population 6 ; nonetheless, exact figures are unavailable. Furthermore, studies have often linked delays in providing vaccinations, or non‐vaccination, to doctors' lack of knowledge or failure to inform families of the indications for these particular vaccines 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Health authorities have de ned chronic neurological diseases as high-risk conditions for in uenza and pneumococcal infections, and they recommend vaccines against these infections (2). Although children with chronic diseases face greater risks, their vaccine coverage rates appear to be lower than in the general population (3); nonetheless, exact gures are unavailable. In previous studies, it was revealed that patients with chronic neurological diseases were vaccinated more delayed and less frequently than the healthy population (1,4,5).…”
Section: Introductionmentioning
confidence: 99%